2016
DOI: 10.1037/edu0000043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of critical discussions on middle school students’ written historical arguments.

Abstract: In this experimental study, 151 middle school students explored 3 historical controversies, first reading and discussing primary source documents in groups, then writing arguments on their own. Students were either randomly assigned to an experimental condition, using argumentative schemes and critical questions as guides during discussions, or to a comparison condition in which a traditional set of questions was used to guide discussions. Students in both conditions read the same historical controversies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 62 publications
0
26
0
5
Order By: Relevance
“…This research has indicated that students in this age group may encounter particular challenges when tasked to integrate information across multiple information resources and evaluate the quality of those resources, especially when trying to judge the credibility of the sources in light of specific source features (e.g., author competence). Moreover, several researchers have studied argumentative reasoning about multiple perspectives or multiple resources, as displayed in written products, in this age group (e.g., Kuhn & Crowell, 2011;Schwarz, Neuman, Gil, & Ilya, 2003;Wissinger & De La Paz, 2016). In this research, it has been found that without extensive intervention, preferably in the form of collaborative dialogic argumentation about ill-structured problems or controversial issues (Bråten Muis, & Reznitskaya, 2017;Kuhn, 2015Kuhn, , 2018, students tend to disregard counterarguments and rebuttals and fail to integrate opposing arguments to reach a more balanced conclusion.…”
Section: Prior Researchmentioning
confidence: 98%
“…This research has indicated that students in this age group may encounter particular challenges when tasked to integrate information across multiple information resources and evaluate the quality of those resources, especially when trying to judge the credibility of the sources in light of specific source features (e.g., author competence). Moreover, several researchers have studied argumentative reasoning about multiple perspectives or multiple resources, as displayed in written products, in this age group (e.g., Kuhn & Crowell, 2011;Schwarz, Neuman, Gil, & Ilya, 2003;Wissinger & De La Paz, 2016). In this research, it has been found that without extensive intervention, preferably in the form of collaborative dialogic argumentation about ill-structured problems or controversial issues (Bråten Muis, & Reznitskaya, 2017;Kuhn, 2015Kuhn, , 2018, students tend to disregard counterarguments and rebuttals and fail to integrate opposing arguments to reach a more balanced conclusion.…”
Section: Prior Researchmentioning
confidence: 98%
“…In such cases, a goal is to avoid pseudo-agreements or pseudo-disagreements (Jucks and Paus, 2013) and to focus the discussion on the true source of differences in opinion. Consequently, asking critical questions seems to play a pivotal role in the context of knowledge construction (Chinn and Osborne, 2008) and for developing insights into not only sciencerelated issues (Mayweg-Paus et al, 2016b;Thiebach et al, 2016) but also history (Wissinger and De La Paz, 2016) and public policy (Song and Ferretti, 2013).…”
Section: Types and Goals Of Dialoguementioning
confidence: 99%
“…However, while reflecting on how best to use the Walton model pedagogically, it did not seem productive to teach students how to recognize 60þ forms of argument (i.e., argument schemes). Some researchers have focused on teaching just two or three schemes (Song & Ferretti, 2013;Wissinger & De La Paz, 2016). I have aimed instead on just teaching the critical questions because it is these questions that do the heavy lifting of evaluating arguments (Dove & Nussbaum, 2017).…”
Section: Waltonmentioning
confidence: 99%